Роль макро- і мікротопонімів у розв’язанні проблеми прабатьківщини слов’ян - Лучик, Василь (Nazwy terenowe i miejscowe w przestrzeni fizycznej, 2016)
Ancient macro- and microtoponyms play an important role in the establishment of the fatherland of the Slavs. Thus the entire complex of extra-linguistic and endo-linguistic factors must be taken into consideration in the process of searching the antique cradle of the Great Slavs as an ethnos.